Realism and Sade - Araujo, Renata Lopes (Lettres Françaises, 2020)
This paper aims to analyze how Sade’s texts, through the use of certain elements employed by literary Realism such as detailed description and the proposal to organize reality by a different point of view, seem to be aimed at getting the reader to rethink what he considers absolute truth, even if the Marquis is considered a writer far from intending to give his work any reality effect.